What is the Meaning of Lifelong Libraries? - M. Tayfun Gülle (Türk Kütüphaneciliği)
This article based on revised of lecture due to 50th Library Week given at Yozgat Bozok University. In the article, lifelong libraries issue is described within the framework of knowledge concept with examples from different applications and services.